Mixed mandates: issues concerning organizational and statutory definitions of terrorism in the United States - McCann, Wesley S. (Terrorism and political violence, 2020)
Defining terrorism continues to be a problematic task for scholars, politicians, and government officials. Research has shown that developing a single definition of terrorism is not only unlikely, but also quite difficult. Definitions of terrorism can arguably be influenced by cultural, social, and political factors. This study qualitatively examines state criminal law and federal organizational definitions of terrorism to discern what elements are commonly seen across such definitions. Furthermore, this article examines what issues arise due to the differences and similarities between and across these groups of definitions. This study finds that organizational definitions are seemingly tied to institution mission or mandate, whereas state definitions are sporadic, lacking consensus, and are evidently influenced by major events such as the September 11 attacks. Across organizational and state definitions of terrorism, “violence,” “fear, terror,” and “target” were the most common elements included. However, other definitional elements exhibited different trends when comparing organizational and state definitions of terrorism. Overall, defining terrorism will continue to be a problem in all arenas as long as the definition is allowed to change due to external factors or influences.